The Role of Combined Anterior Retropharyngeal Approach and Posterior Fixation in Surgical Treatment of Upper Cervical Lesions - Ahmed El-Kholy (Egyptian Spine Association, 2015)
Background Data: Surgical exposure of the upper cervical spine is considered difficult due to the presence of essential and vital nearby structures. Anterior retropharyngeal approach provides direct and wide exposure to treat different lesions in the upper cervical spine. These lesions usually associated with instability and posterior fixation is commonly used to treat this type of instability. Purpose: To evaluate the role of combined anterior retropharyngeal approach and posterior Fixation in treatment of upper cervical lesions. Study Design: A retrospective clinical case series Patients and Methods: This study included 10 patients with C2 neoplasm in 4 patients and spinal infection in 6 patients. Nurick's scale and neck disability index were used to evaluate the functional outcome among our patients. All patients were surgically treated using combined anterior retropharyngeal approach and posterior fixation in the same operation. Results: By using anterior retropharyngeal approach, open biopsy was performed in 4 patients and 6 patients operated for drainage of the retropharyngeal abscess with debridement and decompression. All patients were operated using posterior fixation in the same anesthesia including cranio-cervical fixation in 6 cases and posterior cervical fixation for C1-C4 in 4 cases by using screws-rod system). During our period of follow up the functional state of all patients was improved, there were only two patients with transient dysphagia. A solid fusion was achieved in all cases. Conclusion: The anterior retropharyngeal approach is feasible and effective in surgical exposure and treatment of upper cervical lesions. Anterior decompression and posterior fixation can be done successfully and safely by using a combined anterior retropharyngeal-posterior approach in the same anesthesia. (2015ESJ090)